Transformation of Regional Public Service Agency Governance Based on Good School Governance Towards Financial Independence of Vocational High Schools - Siraj Siraj; Syamsul Bahri; Putri Meurah Intan; Adinda Desrina (LPPM Universitas Malikussaleh, 2024)
Research focused on the transformation of good school governance towards financial independence is still very limited. This study aims to design priority strategies for the Good School Governance. The research method used is a mixed-method approach with a sequential explanatory design, combining quantitative and qualitative methods applied consecutively. This research is important for creating a governance model that incorporates resource standardization, a business model, and effective and efficient performance indicators, enabling schools to achieve financial independence. The novelty of this study lies in the development of a strategic good school governance, which includes resource standardization, business model, performance indicators, and financial independence. The implementation system aims to strengthen the role of industrial learning in vocational education institutions, particularly, by aligning existing governance structures, including organizational governance, financial governance, and accountability governance.